Mobile Application for the Recommendation of Furniture and Appliances Through Augmented Reality to Improve The User Experience in The Online Shopping Process - Aparicio, Ricardo Alfredo Guevara (2022)
Due to the increase in online shopping, companies are looking to reinvent themselves and improve their ecommerce platforms. However, some users still do not dare to make an online purchase mainly because they cannot physically view the product. As a result of this, innovative technologies have started to emerge. Therefore, this project seeks to improve the customer's user experience, using augmented reality and colour recognition to recommend products in a mobile application. For the development of the application, ARCore was used as a software development kit (SDK) to display products and take measures with augmented reality. In addition, a colour recommendation was implemented using the Palette API (Application Programming Interface) for colour recognition and an algorithm based on colour theory to generate the combinations. The usability of the application was evaluated by a group of users, who completed a form that was based on Nielsen's heuristic principles. The main conclusions of the analysis of the responses are that they would make purchases using the application without having to physically see the product, users understood the purpose of using augmented reality and colour recognition to obtain recommendations. In addition, they were able to use all the functionalities implemented in the application without the need for a user manual, which highlights the minimalist design and ease of use of the application.